How Negative Labor Supply Shocks Affect Training in Firms: Lessons from Opening the Swiss-German Border - Caroline Neuber-Pohl; Damiano Pregaldini; Uschi Backes-Gellner; Sandra Dummert; Harald Pfeifer (Institute of Labor Economics (IZA), 2023)
By exploiting a labor market reform causing an outflow of German workers to Switzerland, we examine the effect of negative labor supply shocks on training in firms using the market for apprenticeships as an example. Analysis of administrative data reveals that the reform led to more apprentices in German firms despite a decrease in apprentice wages. This can be explained by a standard two-factor production model where firms substitute outflowing skilled workers with more apprentices; setting lower wages is possible because of a rising supply of apprentices owing to substantially improved employment prospects after border openings.
Keywords: J21; J22; J61; R23; 330; negative labor supply shock; training effects after worker outflow; wage effects; training incentives; apprenticeship training supply and demand